Dual Polarization Single Port Inset Feed Microstrip Patch Array Antenna - Abd Aziz, Mohamad Zoinol Abidin; Mohd. Shah, Mohd. Syaiful Redzwan; Suaidi, Mohd. Kadim; A. Rahim, Mohd. Kamal (2011)
This paper present the designs of array antenna from type of inset-fed microstrip patch antenna by using single port oriented at 45º and -45º. The antennas are capable to generate dual-polarization radiation pattern centered at 45º and -45º. Combinations of two patches using quarter-wave impedance matching technique has been used to designs the array antennas operate at 2.4 GHz. The designs are simulated using Microwave Office 2004 and were fabricated on FR4 substrate with a dielectric constant εr =4.7, tan δ =0.019 and thickness =1.6mm. The simulation and measurement result have been compared. The 3 design 1x2 array antennas yield a bandwidth greater than 5%. The gain of the proposed antennas is also stable with operated frequency. The result showed that the combination of more patches in array can improve the return loss and gain performances.